2022
DOI: 10.1186/s12885-022-09302-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes following 90Y Radioembolization of neuroendocrine liver metastases: evaluation of the radiation-emitting SIR-spheres in non-resectable liver tumor (RESiN) registry

Abstract: Background The goal of this study was to evaluate efficacy and safety of 90Y radioembolization for neuroendocrine liver metastases (NELM) in a multicenter registry. Methods One hundred-seventy patients with NELM were enrolled in the registry (NCT 02685631). Prior treatments included hepatic resection (n = 23, 14%), arterial therapy (n = 62, 36%), octreotide (n = 119, 83%), cytotoxic chemotherapy (n = 58, 41%), biologic therapy (n = 49, 33%) and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Multiple studies have reported safety and outcomes for TARE treatment of LM. 79,80,[99][100][101][102][103][104] Three large multi-institutional randomized phase 3 trials (SIRFLOX, FOXFIRE, and FOXFIRE-Global) demonstrated that 90 Y TARE in addition to FOLFOX-based chemotherapy does not improve OS or PFS when compared with chemotherapy alone as first-line treatment for unresectable CRC LM. 105,106 A subgroup analysis of the SIRFLOX and FOXFIRE-Global trials demonstrated a 4.9-month increase in median OS in patients with HALLEMEIER ET AL.…”
Section: Tarementioning
confidence: 99%
“…Multiple studies have reported safety and outcomes for TARE treatment of LM. 79,80,[99][100][101][102][103][104] Three large multi-institutional randomized phase 3 trials (SIRFLOX, FOXFIRE, and FOXFIRE-Global) demonstrated that 90 Y TARE in addition to FOLFOX-based chemotherapy does not improve OS or PFS when compared with chemotherapy alone as first-line treatment for unresectable CRC LM. 105,106 A subgroup analysis of the SIRFLOX and FOXFIRE-Global trials demonstrated a 4.9-month increase in median OS in patients with HALLEMEIER ET AL.…”
Section: Tarementioning
confidence: 99%
“…Recent prospective registry data and pooled data from published retrospective studies show SIRT can be safely used as an alternative or salvage therapy for NELM, including patients who have undergone surgical resection, multiple prior systemic and arterial therapies, and for relief of symptoms of carcinoid syndrome, with median survival 28-33 months. 2,41,59 Median OS was 33 months in both the CIRT and RESiN registries. In the RESiN registry, well-differentiated tumours had a median OS of 41 months, compared to 13 and 25 months for moderate-and poorly differentiated tumours, respectively.…”
Section: Neuroendocrine Tumourmentioning
confidence: 99%
“…However, the majority of the patients the study of Braat et al had more extensive extrahepatic disease (66%). To date, only Braat et al reported clinical outcomes, indicating the reduction in or resolution of hormone-related complaints in 44% and 34% of patients, respectively [ 9 , 20 , 21 ].…”
Section: Sirt In Nen: Salvage Settingmentioning
confidence: 99%